Cultural Action and Artistic Action: moving territories - Pupo, Maria Lúcia; Veloso, Verônica (Revista Brasileira de Estudos da Presença, 2022)
The article proposes a resumption of the notion of cultural action in the light of the displacements and changes that it has been going through since its emergence in France in the last century, providing clues for the examination of these conceptions in today´s Brazil. From this perspective, the emergence of the notion of artistic action will be analysed, with a view to characterizing – only in a preliminary way – of this field. The distinctions between the two perspectives will be addressed as well as the relationships between them. Both have in common symbolic construction and the establishment of meeting spaces, development of autonomy and reflection.